Pengaruh Financial Knowledge, Perceived Ease of Use Serta Peran E-Commerce Terhadap Minat UMKM dalam Menggunakan Aplikasi Digital Payment - Ni Kadek Mila Damayanti; I Putu Deddy Samtika Putra (Hita Akuntansi dan Keuangan, 2022)
The purpose of this research is to determine the effect of financial knowledge, perceived ease of use, and e-commerce on the interest of SMEs in using digital payments.This research was conducted in Kerambitan District, Tabanan Regency on 1,847 MSME actors and by using the Slovin Formula, a sample of 329 MSME actors was obtained using purposive sampling technique. Primary data collection was carried out by interviewing at the pre-survey stage and also questionnaires. The results of the respondents' answers were then continued with validity and reliability tests. Before performing the multiple linear regression test, the classical assumption test was first tested with SPSS software.The results of the study partially prove that financial knowledge has a positive and significant effect on interest in using digital payments, perceived ease of use has a positive and significant effect on interest in using digital payments, and e-commerce has a positive and significant effect on MSME interest in using digital payments. Suggestions given to MSME actors include attending training on financial knowledge, seeking references from other MSME actors who have used digital payments, and registering their business on existing e-commerce